2017
DOI: 10.1038/srep40446
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia activates Wnt/β-catenin signaling by regulating the expression of BCL9 in human hepatocellular carcinoma

Abstract: The Wnt/β-catenin signaling is abnormally activated in the progression of hepatocellular carcinoma (HCC). BCL9 is an essential co-activator in the Wnt/β-catenin signaling. Importantly, BCL9 is absent from tumors originating from normal cellular counterparts and overexpressed in many cancers including HCC. But the mechanism for BCL9 overexpression remains unknown. Ample evidence indicates that hypoxia inducible factors (HIFs) play a role in the development of HCC. It was found in our study that BCL9 was overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 48 publications
9
70
2
Order By: Relevance
“…BCL9 represents an unexpected addition to previous findings, as a conserved miR-122 target harboring seven miRNA binding sites in coding exons where half contain non-canonical G-bulges. Previous work has shown that BCL9 promotes proliferation and metastases in myeloma and colon cancer cells (Mani et al, 2009), while in HCC, BCL9 inhibition results in reduced proliferation and migration (Xu et al, 2017). We functionally demonstrated that β-catenin transcriptional activity could be repressed by miR-122 through regulation of downstream effector BCL9.…”
Section: Discussionmentioning
confidence: 99%
“…BCL9 represents an unexpected addition to previous findings, as a conserved miR-122 target harboring seven miRNA binding sites in coding exons where half contain non-canonical G-bulges. Previous work has shown that BCL9 promotes proliferation and metastases in myeloma and colon cancer cells (Mani et al, 2009), while in HCC, BCL9 inhibition results in reduced proliferation and migration (Xu et al, 2017). We functionally demonstrated that β-catenin transcriptional activity could be repressed by miR-122 through regulation of downstream effector BCL9.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, hypoxia can increase expressions of β‐catenin, vimentin, VEGF, and c‐met . Nevertheless, the Wnt/β‐catenin signaling pathway activation is associated with hypoxia . Zhi et al provided overwhelming evidence that downregulation of lysosomal degradation of E‐cadherin induced the formation of E‐cadherin/β‐catenin complex and membrane translocation of β‐catenin, indirectly leading to the down‐regulation of cyclin D1 and VEGF, and decline of their malignant functions proliferation, metastasis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…WNT signaling is highly conserved from planarians to humans and serves as a communication system between myriad cell types. [19][20][21] WNT reactivation drives a regenerative or repair response to wounding, either returning the tissue to a fully functional preinjury state or producing nonfunctional fibrotic scar tissue, respectively. 18 WNT signaling can be reactivated locally and transiently as a response to wounding in the kidney and many other tissues.…”
Section: Introductionmentioning
confidence: 99%